A machine learning approach for predicting osmotic coefficients and deriving activity coefficients in alkyl ammonium salts - Rathachai Chawuthai; Siripan Murathathunyaluk; S. Saengsuradech; A. Nukaew; L. Simasatitkul; Suksun Amornraksa; Suttichai Assabumrungrat; Amata Anantpinijwatna (Scientific Reports, 2026)
Quaternary Ammonium Salts (Quats) have diverse applications across various domains. They are extensively used as phase-transfer catalysts (PTCs) in chemical reactions, facilitating the transfer of reactants between aqueous and organic phases. Their unique structure enables the formation of ion pairs, enhancing reaction rates at phase boundaries. This research develops a novel method for predicting Quats' osmotic coefficients using Simplified Molecular Input Line Entry System (SMILES) notation and supervised machine learning. A comprehensive dataset of 1,654 data points from 52 distinct Quats was compiled. The structural characteristics were encoded using SMILES notation. The data was evaluated using random splitting and Leave-One-Group-Out (LOGO) validation to train seven machine learning algorithms. Gaussian Process (GP) emerged as the optimal algorithm. The GP model achieved a mean absolute percentage error (MAPE) of 5.29% and root mean square error (RMSE) of 0.034. Comparisons with Electrolyte-NRTL and Extended UNIQUAC models demonstrate that this data-driven approach offers competitive accuracy while enabling generalization to structurally similar compounds. This work marks a significant starting point for the machine learning-enhanced prediction of activity coefficients, with considerable potential for future refinement and application.
Keywords: Machine Learning in Materials Science; Microwave-Assisted Synthesis and Applications; Chemistry and Chemical Engineering